New species of scale worms of the genus Bylgides (Annelida: Polynoidae) and Pholoe (Annelida: Sigalionidae) from the Brazilian coast - Ogawa, Namy; Miranda, Vinícius Da Rocha; Rizzo, Alexandra E. (Zootaxa, 2025)
Records of polychaetes belonging to Sigalionidae and Polynoidae are scarce along the Brazilian coast, with most reports dating from more than a decade ago. Herein we present the description of three new species, two Polynoidae and one Sigalionidae, sampled during three different environmental monitoring projects, conducted along the states of Sergipe, Rio de Janeiro and São Paulo. The polynoids newly described belong to the genus Bylgides and it is the first occurrence of the genus in the South Atlantic. Bylgides samueli sp. nov. differs from its congeners in having all notochaetae smooth, dark spots covering almost the entire prostomium, lateral projections to the eyes, median antenna and palps smooth, no nephridial papillae from segment 12, and fluorescence. Bylgides cinthyae sp. nov. is distinguished by its smooth elytra partially covering the dorsum, serrated notochaetae with grooves, absence of lateral projections near the eyes and by lacking fluorescence. The third new species belong to the genus Pholoe (Sigalionidae). Pholoe amandae sp. nov. differs from other species in the absence of lateral antennae, ventral cirri with subdistal constriction, neuropodia with stylodes, spiniger chaetae in first chaetiger, elongated falcigers in the first two chaetigers, and a globular facial tubercle with papillae on the posterior margin. Furthermore, a key and a synoptic table for the species of Bylgides and a key for the species of Pholoe are presented herein.